Perfil epidemiológico da leishmaniose visceral em cães diagnosticadosno laboratório da Escola de Veterinária da Universidade Federal de MinasGerais, Belo Horizonte, 2004-2008 - Debora Nunes Papa (2010)
From 2004 to 2008, 6.343 dogs of Belo Horizonte city (BH) were examined to identify seropositiviy of visceral leishmaniosis. The tests were performed at the Laboratory of Zoonosis of the Veterinary School, Federal University of Minas Gerais. A database was created andanalised taking into consideration gender, breed, age and origin of the dogs according to each sanitary district of BH. The majority of the dogs examined were females (54.2%); 26.2 % were mongred dogs ; 29.2% were between 1 and 3 years old and 29.2% were from the PampulhaDistrict. Using the enzyme-linked immuno sorbent assay (ELISA), 29.2% of the dogs were seropositive, 58.1% were negative and 12.3% gave intermediate readings. Using an immuno fluorescence test (IFT), it was found that 31.3% of the dogs were seropositive, 53.4% were seronegative, and 14.6% gave a intermediate result. Among the serologically positive case, 32.9% were males, 22.7% were mongred dogs and 34.2% of dogs aged 1 to 3 years old. Most of the infected dogs were from the North, the Barreiro and the Northwest districts. Results from private laboratories could be obtained in order to add information to the official data from the public lab, to determine actions against the disease.